Triple-Endobutton and clavicular hook: A propensity score matching analysis - Zhang Sujie (De Gruyter, 2021)
We retrospectively analyzed the clinical data of 635 patients with acute acromioclavicular dislocation, who underwent surgery in our hospital between May 2014 and June 2020. Patients were divided into group A (clavicular hook plate) and group B (Triple-Endobutton plates via double-incision). The propensity score analysis using one to one match was performed for comparisons. We obtained 292 matched patients’ data. The matched preoperative clinical characteristics were a balance between the two groups. All clinical parameters showed insignificant differences (P > 0.05). Compared with group A, group B has longer operative time (P < 0.001) and more blood loss (P < 0.001); however, the mean incision length (P < 0.001) and length of hospitalization (P < 0.001) were shorter in group B than in the group A. The mean VAS in group B were significantly lower than in group A at each time point (P < 0.001), and the UCLA shoulder score was higher in the group B. The CMS scores were also higher in group B than in group A, including before removal and 12 weeks after removal (P < 0.001). The clinical efficacy of the double-incision Triple-Endobutton plate is better than the clavicular hook plate technology, and achieves anatomical reduction by reconstructing coracoclavicular ligament.